Environmental taxation, inequality and Engel’s Law: the double dividend of redistribution - Klenert, D; Schwerhoff, G; Edenhofer, O; Mattauch, L (Springer Verlag, 2016)
Empirical evidence shows that low-income households spend a high share of their income on pollution-intensive goods. This fuels the concern that an environmental tax reform could be regressive. We employ a framework which accounts for the distributional effect of environmental taxes and the recycling of the revenues on both households and firms to quantify changes in the optimal tax structure and the equity impacts of an environmental tax reform. We characterize when an optimal environmental tax reform does not increase inequality, even if the tax system before the reform is optimal from a non-environmental point of view. If the tax system before the reform is calibrated to stylized data—and is thus non-optimal—we find that there is a large scope for inequality reduction, even if the government is restricted in its recycling options.